Supporting policy and practice in Ontario through ICES’ Applied Health Research Question (AHRQ) Program - Ishiguro, Lisa; An, Diana; Plumptre, Lesley; Paul, Jenine; Mecredy, Graham; Li, Kathy; Ho, Minnie; Bronskill, Susan; Victor, Charles; Schull, Michael; Paterson, Michael (International Journal of Population Data Science, 2021)
ICES upholds a strong reputation for generating high-quality evidence to inform policy and practice through its collaborations with a broad range of health system stakeholders including government policymakers and healthcare providers including clinicians. Supported by the Ontario Ministry of Health and Ministry of Long-Term Care, the ICES Applied Health Research Question (AHRQ) Program leverages the data holdings and, scientific and clinical expertise to generate evidence tailored to the information needs of requestors. This paper outlines the approach, process, strengths, challenges and the resulting influence and impact to the healthcare landscape in Ontario.